Peran Probiotik Dalam Kesehatan Pencernaan Manusia - Ubaidilah, Achsin (Lembaga Publikasi Ilmiah Nusantara, 2025)
Probiotics are live microorganisms that, when consumed in adequate amounts, confer health benefits to the host, particularly in maintaining and enhancing digestive health. Research on probiotics has shown that their presence can help maintain the balance of gut microbiota, improve intestinal barrier function, and play a role in modulating both local and systemic immune systems. This article examines the role of probiotics from various genera, such as Lactobacillus, Bifidobacterium, and Saccharomyces, in supporting human digestive health, including their potential in preventing and managing gastrointestinal disorders such as diarrhea, irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD). Furthermore, the article discusses factors that influence the effectiveness of probiotics, such as dosage, duration of consumption, and strain compatibility with individual conditions. This review also highlights challenges in the development of probiotic products, including stability during storage and resistance to gastrointestinal conditions. Based on the available scientific evidence, probiotics hold great potential as adjunctive and preventive therapeutic agents for maintaining digestive system health. However, more large-scale, controlled clinical studies are needed to ensure the safety, effectiveness, and specific mechanisms of action of each probiotic strain within a broader human population context.